PENGARUH PENGALAMAN KERJA, PELATIHAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN NITRA JAYA KONVEKSI - Pramanta, Made Deni; Dewi, A.A Sagung Kartika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023, 2023)
The purpose of this study was to analyze the effect of work experience, training and motivation on work productivity. This research was conducted in Nitra Jaya Confection. The number of samples used is 38 employees of Nitra Jaya Confection, with the method of determining the sample is Non Probability Sampling. Data was collected using a questionnaire using a 5 point Likert Scale to measure 23 questions and analyzed using Multiple Linear Regression analysis techniques. In this study, the theory used is Maslow's Need Hierarchy Theory. The results of this study indicate that the variables of work experience, training and motivation have a positive and significant effect on the work productivity of Nitra Jaya Confection employees. The theoretical implications of this research have been able to explain the theoretical model used as the basis for formulating hypotheses, namely the influence of work experience, training and motivation on the work productivity of Nitra Jaya Confection employees